1977
DOI: 10.1002/zaac.19774310104
|View full text |Cite
|
Sign up to set email alerts
|

Beiträge zur Chemie des Phosphors. 65. Zur Kenntnis der Cyclo‐carba‐phosphane (PC6H5)4CH2, (PC6H5)4CH2S und (PC6H5)4CH2S2

Abstract: Bei der Reaktion von 1,2,3,4‐Tetraphenyl‐cyclo‐5‐carba‐1,2,3,4‐tetraphosphan (PC6H5)4CH2 1 mit Schwefel im Verhältnis 4 C6H5P:1 S bzw. 2 C6H5P:1 S entstehen die Thio‐cyclo‐carba‐phosphane (PC6H5)4CH2S 2 bzw. (PC6H5)4CH2S2 3. Die Schwefelatome in 2 und 3 sind exocyclisch an den der CH2‐Gruppe benachbarten Phosphoratomen gebunden, was ein Indiz für die Stabilität des P4C‐Ringgerüstes ist. Bezüglich der Phenylsubstituenten weisen 1, 2 und 3 „all‐trans”︁‐Konfiguration auf. Die 31P‐ und 1H‐NMR‐Parameter für 1 und 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

1977
1977
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 8 publications
2
7
0
1
Order By: Relevance
“…Coupling along the edge of a five-membered ring is much more effective ( 1 J P1,P2 % 280 Hz) than coupling between two phosphorus atoms sharing a three-membered ring structure ( 1 J P2,P3 % 150 Hz). [12] The atoms P4 and P5 do not show 1 J P,P coupling and are differentiated by the characteristic chemical shift of sp 2 -hybridized P5. [5] Following the demands of theory, the enantiomeric mixture 8A C H T U N G T R E N N U N G (R+S) and its isolated enantiomer 8 are indistinguishable by NMR spectroscopy in achiral media.…”
Section: Nmr Spectroscopymentioning
confidence: 99%
“…Coupling along the edge of a five-membered ring is much more effective ( 1 J P1,P2 % 280 Hz) than coupling between two phosphorus atoms sharing a three-membered ring structure ( 1 J P2,P3 % 150 Hz). [12] The atoms P4 and P5 do not show 1 J P,P coupling and are differentiated by the characteristic chemical shift of sp 2 -hybridized P5. [5] Following the demands of theory, the enantiomeric mixture 8A C H T U N G T R E N N U N G (R+S) and its isolated enantiomer 8 are indistinguishable by NMR spectroscopy in achiral media.…”
Section: Nmr Spectroscopymentioning
confidence: 99%
“…17 This may explain why a second isomer of 2•2S was not observed by Baudler and co-workers in solution. 7 Although the solution behaviour of 3 can certainly not be regarded as trivial, the 31 P{ 1 H} NMR spectrum of 4 reveals a much more complicated situation (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, while BH 3 complexes of cyclooligophosphanes have remained elusive, Baudler et al reported reactions of the cyclooligophosphanes cyclo-(P 4 Ph 4 CH 2 ) (2) and cyclo-(P 5 Ph 5 ) (5) with elemental sulfur to give the sulfides cyclo-(S 2 P 4 Ph 4 CH 2 ) (2•2S) 7 and cyclo-(SP 4 Ph 4 ). 8 )]OTf (R, R = Me, Ph) can be prepared by reaction of cyclooligosphanes with phosphenium triflates or methyl triflate.…”
Section: Introductionmentioning
confidence: 99%
“…This resulted in longer reaction times and the formation of a two-phase system. 31 P-NMR spectra of the lower phase after a reaction time of 18 h revealed 5 sets of different peaks which could be attributed to the diastereomers (1a,Z)/(1b,E), compound (2) in addition to the intermediate (3a)/(3b). By comparing the coupling nature of the NMR shifts of the intermediates with those of compound (1a,Z)/(1b,E), we were able to elucidate structural information.…”
Section: Synthesis/preparationmentioning
confidence: 97%